Pesantren Graduates and Social Mobility in the Global Era: Roles and Challenges - Af’idah, Irma Nur; Nisfa, Nia Lailin (Santri: Journal of Pesantren and Fiqh Sosial, 2025)
This study aims to explore the integration of pesantren graduates into society and the labor market based on key indicators that determine successful integration. Employing a qualitative approach, data were collected through purposive sampling involving participants who had completed their education at the Madrasah Aliyah level (Senior High School) within pesantren institutions. Data validity was ensured through the triangulation of theories and sources, while data analysis involved the stages of data collection, reduction, and drawing conclusions. The findings reveal that pesantren graduates demonstrate in-depth religious knowledge, strong discipline, collaborative skills, and economic independence comparable to the general population. Importantly, their consistent exposure to structured and disciplined environments not only enables them to compete effectively in the job market but also to adapt to technological advancements, reassuring their potential in the ever-evolving job market.